Penerapan Metode Diskusi Simposium Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas XI F 7 Pada Mata Pelajaran PAI Di SMAN 1 Kecamatan Payakumbuh Tahun Pelajaran 2024-2025 - Hendri, Jon (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve the learning outcomes of 11th-grade students in class XI F 7 at SMAN 1 Payakumbuh in Islamic Religious Education through the application of the symposium discussion method. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results showed a significant improvement in student learning outcomes. The average score in the first cycle was 73.4, which increased to 86.66 in the second cycle. The application of the symposium discussion method proved effective in enhancing students' activeness in asking questions, engaging in discussions, and expressing opinions. These findings align with social learning theory and collaborative learning, which emphasize the importance of active interaction in the learning process. Therefore, this method can be considered an alternative approach to enhance students' learning outcomes and social skills.